Pre-formulation Study of Salicylidine-cephalexin-Zn(II) dihydrate, a New Derivative of Cefalexin - Iqbal, M. S.; Khan, A. H. (Drug Research, 2016)
Background: Salicylidine-cefalexin-Zn(II)·2H2O, a new derivative of cefalexin, has been reported to possess enhanced anti-microbial activity and lower toxicity than cefalexin. It is, therefore, desirable to carry out a pre-formulation study to determine its pharmaceutical properties which will be useful in conversion of the new molecule into various dosage forms.Methods: The compound was synthesized by the previously reported method and characterized by elemental, Fourier-transform infrared and electronic spectral analyses. Crystallinity was determined by powder x-ray diffraction. Particle size distribution was determined by a laser-based sizer. Other properties including flow, density and compaction strength were determined by use of appropriate standard methods. The compound was also evaluated as a prodrug through dissolution study by the USP method.Results: It was found that the new derivative is an amorphous powder with different bulk density, porosity, compressibility, plasticity and flow properties as compared to cefalexin. The amorphous character of the new compound suggests that it will have better bioavailability. The dissolution study indicated that this compound is hydrolyzed to produce cefalexin in water in a sustained manner, thus it will act as a prodrug in vivo. The release data fitted well into Highuchi model.Conclusion: Various pharmaceutical properties essentially required for formulation of salicylidine-cefalexin-Zn(II)·2H2O into dosage forms were determined. This study has shown that the new drug would behave as a prodrug for cefalexin with better bioavailability.
Keywords: cefalexin; cefalexin complexes; Schiff base complexes; zinc complexes